ANALYSIS OF THE EFFECTIVENESS OF THE POWER GENERATOR ON THE FISHING VESSEL KM. BINAMA 03 USING THE OVERALL EQUIPMENT EFFECTIVENESS (OEE) APPROACH - Demeianto, Bobby; Abrori, M. Zaki Latif; Rusdianovi Caniago, Renaldi; Preston Siahaan, Juniawan; Tumpu, Mula (Aurelia Journal, 2024)
Although many studies have been conducted on the effectiveness of a generator or machine using the OEE (Overall Equipment Effectiveness) method, research focusing on the effectiveness of electrical generators on fishing vessels has been limited. This study aims not only to measure the effectiveness of the KM. Binama 03 generator but also to provide data-driven recommendations to enhance equipment reliability in the future. The study's results showed that the average values of Availability, Performance Efficiency, Rate of Quality, and Overall Equipment Effectiveness for the KM. Binama 03 generator in February, March, and July were 97.76%, 81.36%, 79.50%, and 63.49%, respectively. These figures indicate that the OEE values of the KM. Binama 03 generator during operations in these months were still below the JIPM (Japan Institute of Plant Maintenance) minimum standard of 85%. The findings of this research are expected to provide valuable insights for maximizing the effectiveness of equipment or machinery, as the primary goal of Total Productive Maintenance (TPM) is to ensure that machines remain in optimal condition without disrupting daily activities. This can only be achieved through preventive and predictive maintenance of the equipment.